The Principals’ Role As Instructional Leaders in The Implementation of Deep Learning in Elementary Schools in Pekanbaru - Tessa Silvani; Maya Novita Sari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study explores the role of school principals as instructional leaders in elementary schools in Pekanbaru in promoting the implementation of Deep Learning (DL). This role was examined through three principal functions of school principals as instructional leaders: (1) establishing a school vision to strengthen the dimensions of learning environments and learning partnerships; (2) conducting academic supervision to support pedagogical practices and the utilization of digital technology; and (3) developing teacher competencies to enhance teachers’ readiness to implement the DL framework comprehensively. This study employs a descriptive qualitative approach, using interviews and document analysis, involving principals from six elementary schools with A and B accreditation statuses. Participants were selected through purposive sampling, and triangulation was achieved through teachers and school supervisors. The findings indicate that a participatively formulated and consistently communicated vision influenced the direction of DL implementation, particularly in preparing supportive learning environments and fostering partnerships with parents and the community. Academic supervision based on DL indicators and supported by coaching-oriented feedback was found to improve teachers’ pedagogical quality and their utilization of digital technology. Furthermore, competency development through contextual training, professional learning communities, and a psychologically safe climate significantly enhanced teachers’ readiness to implement the DL framework. Conversely, in schools with limited institutional capacity, the uneven internalization of the school vision, supervision practices that remained administrative in nature, and limited dissemination of training outcomes emerge as major barriers to the consistent implementation of DL.